How to Apply Local Wisdom Value Systems in Management Practices and School Culture? A Study of Internalization and Implementation Practices in School Settings - Hindaryatiningsih, Nanik; Ahiri, Jafar; Karno, Edy; Munadi, La Ode Muh. (Journal of Ecohumanism, 2025)
This study investigated the application of local wisdom value systems in management practices and school culture at Senior High School 2 Bau-bau in 2023. Employing a qualitative research method with an ethnographic approach, participants included the head of the education office, supervisors, school principal, teachers, educational staff, students, parents, school committees, and the surrounding community. Data were collected through interviews, document studies, observations, and focus group discussions. The research revealed four systems of Buton local wisdom values, encompassing the outlook on life, knowledge, and life strategies of the Buton community. These values were integrated into the school's vision, influencing management practices, leadership, and teaching models. They also formed the foundation of the school's cultural values, emphasizing religious and general cultural aspects focused on purity, interpersonal values, and self-values. Development strategies included instilling culturally oriented quality values, fostering teamwork, and engaging all stakeholders through environmentally friendly practices, program planning, habituation, spontaneous activities, facility conditioning, and exemplary behaviour. The analysis results indicated a distribution related to social interaction (58.6%), school culture (24.1%), and good behaviour (17.2%), with social interaction being the most significant. The study concluded that Buton's local wisdom values positively contributed to the school's vision, character development, and individual awareness, creating a conducive school climate, good learning outcomes, and a quality culture, driving the school towards positive performance.